2007
DOI: 10.1017/s0022215107000734
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties of operative endoscopes used in otorhinolaryngology

Abstract: The heat produced by some endoscopes is sufficiently great to cause thermal injury to tissues. Awareness of the temperatures produced by these endoscopes should prompt clinicians to actively cool their endoscopes during a procedure, before any thermal injury is caused.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
49
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 12 publications
4
49
0
1
Order By: Relevance
“…The matter of the heat generated by endoscopes in ENT has been raised in a previous article in The Journal by MacKeith and colleagues 5 in 2008, and has been taken up by colleagues in Birmingham in this issue, 6 specifically in relation to potential thermal dangers in endoscopic ear surgery. They conclude that the danger is real and give some useful tips on how to minimise the damage to tissues.…”
mentioning
confidence: 98%
“…The matter of the heat generated by endoscopes in ENT has been raised in a previous article in The Journal by MacKeith and colleagues 5 in 2008, and has been taken up by colleagues in Birmingham in this issue, 6 specifically in relation to potential thermal dangers in endoscopic ear surgery. They conclude that the danger is real and give some useful tips on how to minimise the damage to tissues.…”
mentioning
confidence: 98%
“…6 A 1998 study in Scotland describes the highest endoscope temperature at 10 minutes at 95 C but a significant rise with the exposed fiberoptic light cord reaching a peak of 225 C. 7 MacKeith et al in 2007 used a calibrated thermocouple to measure the temperatures of 4-mm and 3-mm 0 , 30 , and 70 rigid Storz endoscopes. 8 This recorded a maximum temperature of 104. 6 C with the larger diameter 0 scopes being the hottest with 80% of the increase taking place in the first 35 seconds, but the study fails to document the specific models, dates, and wattage of the equipment utilized.…”
Section: Discussionmentioning
confidence: 93%
“…This article does give specific recommendations to cool the endoscope at appropriate intervals and avoid tissue contact as much as possible to minimize risk of injury. 8 The majority of the heat generated is largely due to the radiated power in the visible light spectrum. 7 We theorized that as equipment gets older with damage to the fiberoptics, potentially dangerous temperatures may be created.…”
Section: Discussionmentioning
confidence: 99%
“…Higher light source power and intensity lead to higher maximal scope tip temperatures. [2][3][4][5] Although using lower power light sources and reduced intensities may decrease scope tip temperatures, this comes at the expense of decreased illumination and intraoperative visualization. Light source manufacturers generally recommend using the lowest light source intensity that allows adequate illumination.…”
Section: Discussionmentioning
confidence: 99%
“…1 Other sources have shown that the tips of rigid nasal endoscopes can reach temperatures greater than 40°C, and therefore may lead to thermal tissue injury during endoscopic sinonasal surgery. [2][3][4] Scope irrigation sheaths are generally used to improve intraoperative visualization (Fig. 1).…”
mentioning
confidence: 99%